Art Practices and Urban Promenades: Belgrade's Knez Mihailova Street vs. Dionysius the Areopagite Promenade in Athens - Žakula (Serbia), Sonja; Đorđević Crnobrnja (Serbia), Jadranka (Bulletin of the Institute of Ethnography SASA, 2018)
Art Practices and Urban Promenades: Belgrade's Knez Mihailova Street vs. Dionysius the Areopagite Promenade in Athens